On the Influence of Collector Size on the Solar Chimneys Performance - Al-Azawiey, S.S. (EDP Sciences, 2017)
Performance of solar chimney power plant system is highly influenced by the design geometries. The collector size is logically enhances the solar chimney performance, but the trend of enhancement is not yet investigated. In the present work, experimental and numerical investigations have been carried out to ascertain, in terms of qualitative and quantitative evaluation, the effect of the collector diameter. Daily thermal efficiency has been determined at four different collector diameter. Two different collector diameters, 3.0 and 6.0 m, have been investigated experimentally, and then scaled up, to 9.0 and 12.0 m, by numerical simulation using ANSYS-FLUENT®15 software. Results demonstrated that collector diameter has effectively influenced the system performance. Larger collector diameter imposed increase in the velocity, temperature and the daily average thermal efficiency of the system. From the experimental results, increasing the collector diameter from 3.0 to 6.0 m has increased the daily average thermal efficiency of the collector from 9.81 to 12.8. Simulation results at 800 W/m2 irradiation revealed that the velocity in the chimney have increased from 1.66 m/s at 3.0 m collector diameter to 2.34, 2.47 and 2.63 m/s for 6.0, 9.0 and 12.0 m collector diameters, respectively. © The authors, published by EDP Sciences, 2017.